Model Kepemimpinan Strategik dan Pengelolaan Sumber Daya Nasional Untuk Pertahanan Adaptif Indonesia Emas 2045 - Nijo, Jamet; Lubis, Zulhamidi; Susilo, Tarsisius; Supriyo, Sarwo; Risandi, Anton Bimo (Syntax Literate, 2025)
This article analyzes the model of strategic leadership and national resource management as the foundation for Indonesia’s adaptive defense toward Golden Indonesia 2045. The study is based on global dynamics marked by geopolitical rivalries, technological progress, and multidimensional threats that demand visionary and integrative leadership. A qualitative-descriptive method was employed, combining literature review, policy analysis, and comparative international case studies, with data drawn from books, academic journals, official defense documents, and expert interviews. SWOT analysis reveals Indonesia’s strengths in ideology, geostrategy, and social legitimacy, yet highlights weaknesses in defense modernization, foreign technology dependence, and limited cross-sectoral coordination. Strategic opportunities lie in the Golden Indonesia 2045 vision, digital transformation, and international cooperation, while external threats include great-power rivalries, cyberattacks, grey-zone competition, and global supply chain disruptions.The study concludes that Indonesia’s strategic leadership must be transformational, adaptive, and integrative. Recommendations focus on building an independent defense industry, strengthening human resources, and advancing digital defense. With consistent implementation, this model can enhance adaptive defense and contribute significantly to achieving Golden Indonesia 2045.